Prevalence of microbiological markers in bone tissue from live and cadaver donors in the musculoskeletal tissue bank of Passo Fundo - Bruno Dutra Roos; Milton Valdomiro Roos; Antero Camisa Júnior; Ezequiel Moreno Ungaretti Lima; Rafael Noshang Pereira; Maurício Luciano Zangirolami; Gisela Machado de Albuquerque (Revista Brasileira de Ortopedia, 2014)
Objective:To conduct an epidemiological analysis on the main microbiological markers in bone tissue that was processed at the musculoskeletal tissue bank of Hospital São Vicente de Paulo, in Passo Fundo, between August 2007 and October 2011.Methods:Between August 2007 and October 2011, 202 musculoskeletal tissue samples were collected for the tissue bank. Among these, 159 samples were from living donor patients and 43 were from cadaver donors. The following serological tests were requested: hepatitis B, hepatitis C, syphilis, cytomegalovirus, Chagas disease, toxoplasmosis, HIV and HTLV.Results:Among the 159 living donors, 103 (64.75%) were men and 56 (35.25%) were women. The patients' mean age was 59.35 ± 8.87 years. Out of this total, 76 tissue samples (47.8%) from donors were rejected. There was no difference in the number of rejections in relation to sex (p = 0.135) or age (p = 0.523). The main cause of rejection was serologically positive findings for the hepatitis B virus, which was responsible for 48 rejections (63.15%). Among the 43 cadaver donors, the mean age was 37.84 ± 10.32 years. Of these, 27 (62.8%) were men and 16 (37.2%) were women. Six of the samples collected from cadaver donors were rejected (13.9%), and the main cause of rejection was serologically positive findings for the hepatitis C virus, which was responsible for three cases (50%). There was no significant difference in the number of rejections in relation to sex (p = 0.21) or age (p = 0.252).Conclusion:There were a greater number of rejections of tissues from living donors (47.8%) than from cadaver donors (13.9%). Among the living donors, the main cause of rejection was the presence of serologically positive findings of the hepatitis B virus, while among the cadaver donors, it was due to the hepatitis C virus.